Guidance Note on the New Design for Article IV Consultation Reports. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Earlier in 2011, Management approved a new design covering both the design and structure for stand-alone Article IV staff reports. All stand-alone Article IV reports issued to the Board after September 1 are being prepared in the new format. It is anticipated that this new design will be rolled out gradually over the course of the next fiscal year for other country reports and policy documents.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Appraisal; Article IV Report; PP; Report; Staff Appraisal